PERLINDUNGAN HUKUM DAN HAK MEMPEROLEH KESELAMATAN KERJA BAGI TENAGA KESEHATAN AKIBAT PANDEMI COVID-19 - Dwi Armeilia (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
Medical workers are a noble profession, especially amid the Covid-19. One of the aspects that have received the most impact from this pandemic is in the health sector. The problems in the health sector have become increasingly dangerous in the era of the Covid-19 Pandemic in Indonesia. The current condition is a concern for all people regarding efforts to control and overcome the Covid-19 Pandemic in Indonesia. This includes doctors and other health professionals. The number of deaths of medical personnel, especially doctors and nurses, is increasing. This research focuses on Indonesia's legal policies regulating protection and the fulfillment of safety work rights for health workers who are dealing with the pandemic. The legal method used in this research is normative legal research. The results show that legal protection and fulfillment of the right to safety for medical personnel have been regulated in legislation. However, these provisions do not specifically regulate the potential dangers of the spread of the Covid-19 virus.